GENDER DALAM PERSPEKTIF ISLAM - SIRI, HASNANI (AL-MAIYYAH, 2014)
Gender is one of the fenomenal opinion that talks a lot in the world. There are many options to understand about Gender but it will difficult to combine the form of definition because some people think that the differtent between the men and the women is seen by the sex attribute. Gender is the diffeternt between the men and the women that should be understood based on the construct of society in value and act. Gender in the Islamic perspective in seeing the different between the men and the women when they can be the same to live their life by the same opportunity in their duties on domestic as well as in the public. Most important thing is understand that al-Quran an Hadis can give the explanation about the misogynic paradigm in women roles.